2012
DOI: 10.1016/j.ijscr.2012.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Delayed recognition of diaphragmatic injury caused by penetrating thoraco-abdominal trauma

Abstract: A high index of suspicion must be employed for DI in the context of penetrating thoraco-abdominal trauma. Inpatient observation and laparoscopy/thoracoscopy should be considered when radiological findings are ambiguous. Front line physicians should also consider diaphragmatic herniation in stab victims who re-present with respiratory, circulatory, or gastrointestinal symptomology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Therefore, consideration of the potential extent of injuries in patients appears to be more important than simply monitoring the presenting symptoms. For instance, diaphragm injuries in thoraco-abdominal stab wounds are often recognized only after some delay ( 32 ). In such cases, laparoscopic exploration would be a useful approach.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, consideration of the potential extent of injuries in patients appears to be more important than simply monitoring the presenting symptoms. For instance, diaphragm injuries in thoraco-abdominal stab wounds are often recognized only after some delay ( 32 ). In such cases, laparoscopic exploration would be a useful approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although diagnostic thoracoscopy and laparoscopy are recommended, 22 they are minimum invasive approaches for the injured patients. In our opinion, videothoracoscopy should be therapeutic instead of diagnostic.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Emily et al [25], Fabian et al [19], and Heng et al [2] reported fewer complications rate, shorter length of hospital stay, lesser operative time with negative laparoscopy than with negative or non-therapeutic laparotomy.…”
mentioning
confidence: 99%